2019
DOI: 10.3390/agronomy9120838
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis CBR05 for Tomato (Solanum lycopersicum) Fruits in South Korea as a Novel Plant Probiotic Bacterium (PPB): Implications from Total Phenolics, Flavonoids, and Carotenoids Content for Fruit Quality

Abstract: Plant growth-promoting rhizobacteria (PGPR) are naturally occurring soil biota which benefit plants by improving plant productivity and immunity. The aim of the present work was to evaluate the effect of the inoculation of PGPR strain, Bacillus subtilis CBR05 on the quality of tomato fruits produced under greenhouse conditions. Results were compared with mock-inoculated control and market sample. We found a significant increase in total phenol and flavonoid contents of tomato fruits in PGPR strain B. subtilis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
1
22
0
3
Order By: Relevance
“…P. caninum leaf extract is known to suppress blast disease and increase the number of tillers of certain rice hybrids [55]. The inhibition of the fungal pathogen may also be due to the antagonistic activity of B. subtilis present in liquid biofertilizer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. caninum leaf extract is known to suppress blast disease and increase the number of tillers of certain rice hybrids [55]. The inhibition of the fungal pathogen may also be due to the antagonistic activity of B. subtilis present in liquid biofertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the yield of rice due to various treatments is likely due to the addition of liquid biofertilizer that contained different strains of PGPR, such as Enterobacter cloacae, Bacillus subtilis, and Stenotrophomonas maltophilia. This microbial consortium stimulates plant growth, as well as exhibits biocontrol activity, protecting plants from disease, and thus improving crop yield [55]. Kumar [56,57] reported the increase in rice yield following the inoculation of Integral ® , a commercial biofertilizer preparation that contained B. subtilis MBI 600.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the implications of microbial plant biostimulants on improving produce quality, Chandrasekaran et al [61] reported that the inoculation of PGPR strain, Bacillus subtilis CBR05 induced a significant increase in tomato quality in terms of carotenoids profile (β-carotene and lycopene). Finally, Caser et al [62,63] showed that the inoculation of soilless-grown saffron with Rhizophagus intraradices and to a lesser extent with a mixture of R. intraradices and Funneliformis mosseae boosted significantly the synthesis and accumulation of health-promoting molecules such as anthocyanins, polyphenols and vitamin C; antioxidant activity; and important bioactive compounds in saffron, such as crocin II, picrocrocin and quercitrin.…”
Section: The Role Of Non-microbial and Microbial Biostimulants In Impmentioning
confidence: 99%
“…PGPR formulations are a significant biostimulant class, as they allow root growth, mineral availability, and efficiencies in the utilization of nutrients in crop rhizosphere to increase crop growth [45]. Many PGPR is known to stimulate phytohormone production through a combination of various mechanisms [46][47][48][49][50][51][52][53] represented in Table 2.…”
Section: Plant Growth Promotion and Nutrient Acquisitionmentioning
confidence: 99%
“…), pigments (like chlorophyll, carotenoids)and antioxidant substances and therefore, improve plant quality, productivity, and yield[21,[83][84]. As, an example, the impact on bean common plants cultivated under water stress shows substantial enhancement in the phenolic contents of the inoculated plants of four biostimulant products having Bacillus subtilis in their formulations[84].Also, by inoculation of PGPR strain, Bacillus subtilis CBR05, the quality of tomatoes is known to get better for carotenoid profile (carotene and lycopene)[49]. The influence of the bio-preparation containing some bacterial species like Streptomyces sp., Bacillus subtilis, and Pseudomonas fluorescens onto the growth enhancement of fruits through organic farming reported that the growth of sour cherry and apple trees was improved by these bio-preparations[85].…”
mentioning
confidence: 99%